Effect of Rational-Emotive Burnout Management Programme on Occupational Burnout among Health and Physical Education College Teachers in Nigeria - Cosmas, Ugwu, Uchenna; Boniface, Mary; Ifeoma Ofuebe, Justina; Ebere Ogbuabor, Shulamite; Ifeoma Ogidi, Chinenye (International Journal of Psychosocial Rehabilitation, 2021)
Occupational burnout is an adverse reaction to prolonged stress in the workplace. Teachers are among the most vulnerable groups to occupational burnout, particularly in the school system. This study investigated the effect of rational-emotive burnout management intervention (REBMP) on occupational burnout among health and physical education college teachers (HPECTs) in Nigeria. An experimental research design involving a purposive sample of 248 participants who were assigned to either intervention (n = 124) or control (n = 124) groups was adopted. The study was based on pre-posttest measures from August and December, 2019. The REBMP treatment manual was delivered to participants in the intervention group. A standardized teacher burnout inventory scale (TBIS) with a 0.85 reliability index was used for data collection, while IBM SPSS version 22 was used for data analysis. The result showed that REBMP has a significant effect on occupational burnouts of HPECTs. The participants in the intervention group had a lower score (21.78±1.86) in the posttest measure when compared to pretest scores (38.43±0.80). Also, while no significant difference existed between participants in intervention (38.43±0.80) and control groups (32.30±0.09) on teacher burnout inventory scale-TBIS pretest (P=0.108>0.05), significant difference was observed on participants in intervention (21.78±1.86) and control groups (33.21±1.07) on TBIS posttest scores (P=0.019<0.05). In conclusion, psychological and health promotion programs are effective tools for managing occupational burnouts in workplaces and thus should be adopted, particularly in the school system. The adoption of the programs would enhance productivity, job performances, and satisfaction among employees.